PRAKTIK PUBLIC RELATION DALAM PANDANGAN ISLAM - Sulvinajayanti Sulvinajayanti (KOMUNIDA : Media Komunikasi dan Dakwah, 2018)
Practices in public relations activities do not only arrive at the initial step of the meeting, which if the second party is impressed, the public relations work is finished. However, in reality it is only the first step taken so that the next steps can be taken. Public relations practice is not only limited to the creation of a pleasant first impression or what is better known today is imaging, but next is how the pleasant situation can continue in accordance with the objectives to be achieved for example in a company of course the thing to be achieved is to seek profit . One of the main keys to the success of the PR of the Prophet is to build credibility or trust. This can be seen from his history before preaching. He is well-known as a very honest person in the midst of society, so it is called al-amin (trustworthy). Muhammad SAW's competence in preaching also cannot be doubted. This end-time prophet has all the keys to success in da'wah, both in terms of methods, communication techniques, mastery of material, and the ability to understand and explore who he faces. The Prophet Muhammad had the skills of effective communication and the ability to package the message he wanted to convey and was able to influence his interlocutors.